PM2.5 induce lifespan reduction, insulin/IGF-1 signaling pathway disruption and lipid metabolism disorder in Caenorhabditis elegans - Wenjing Zhang; Zinan Li; Zinan Li; Guojun Li; Guojun Li; Ling Kong; Haiming Jing; Haiming Jing; Nan Zhang; Junyu Ning; Junyu Ning; Shan Gao; et al. (Frontiers in Public Health, 2023)
IntroductionExposure to fine particulate matter (PM), especially PM2.5, can induce various adverse health effects in populations, including diseases and premature death, but the mechanism of its toxicity is largely unknown.MethodsWater-soluble components of PM2.5 (WS-PM2.5) were collected in the north of China in winter, and combined in two groups with the final concentrations of 94 μg/mL (CL group, AQI ≤ 100) and 119 μg/mL (CH group, 100 < AQI ≤ 200), respectively. The acute and long-term toxic effects of WS-PM2.5 samples were evaluated in several aspects such as development, lifespan, healthspan (locomotion behavior, heat stress tolerance, lipofucin). DAF mutants and genes were applied to verify the action of IIS pathway in WS-PM2.5 induced-effects. RNA-Sequencing was performed to elucidate the molecular mechanisms, as well as ROS production and Oil red O staining were also served as means of mechanism exploration.ResultsBody length and lifespan were shortened by exposure to WS-PM2.5. Healthspan of nematodes revealed adverse effects evaluated by head thrash, body bend, pharyngeal pump, as well as intestinal lipofuscin accumulation and survival time under heat stress. The abbreviated lifespan of daf-2(e1370) strain and reduced expression level of daf-16 and hsp-16.2 indicated that IIS pathway might be involved in the mechanism. Thirty-five abnormally expressed genes screened out by RNA-Sequencing techniques, were functionally enriched in lipid/lipid metabolism and transport, and may contribute substantially to the regulation of PM2.5 induced adverse effects in nematodes.ConclusionWS-PM2.5 exposure induce varying degrees of toxic effects, such as body development, shorten lifespan and healthspan. The IIS pathway and lipid metabolism/transport were disturbed by WS-PM2.5 during WS-PM2.5 exposure, suggesting their regulatory role in lifespan determination.